A wideband low phase noise VCO design. Issue 1 (July 2021) - Cheng, Ze; Zhang, Dianwei; Li, Weimin
Abstract: A frequency synthesizer with high reliability and low noise was designed and manufactured by 0. 13um SiGe BICMOS process. The frequency synthesizer circuit is capable of generating 7. 5GHz-15GHz RF output signals (the entire VCO output band);The normalized phase noise of the frequency synthesizer reaches-230 dBC / Hz, and the VCO phase noise of the frequency synthesizer reaches-119dBC/Hz@1MHz at the oscillation frequency of 13GHz.